Pathway dependence of ecosystem responses in China to 1.5 °C global warming - Yue, Xu; Liao, Hong; Wang, Huijun; Zhang, Tianyi; Unger, Nadine; Sitch, Stephen; Feng, Zhaozhong; Yang, Jia (Atmospheric chemistry and physics, 2020)
China is currently the world's largest emitter of both CO2 and short-lived air pollutants. Ecosystems in China help mitigate a part of the country's carbon emissions, but they are subject to perturbations in CO2, climate, and air pollution. Here, we use a dynamic vegetation model and data from three model inter-comparison projects to examine ecosystem responses in China under different emission pathways towards the 1.5 ∘C warming target set by the Paris Agreement. At 1.5 ∘C warming, gross primary productivity (GPP) increases by 15.5±5.4 % in a stabilized pathway and 11.9±4.4 % in a transient pathway. CO2 fertilization is the dominant driver of GPP enhancement and climate change is the main source of uncertainties. However, differences in ozone and aerosols explain the GPP differences between pathways at 1.5 ∘C warming. Although the land carbon sink is weakened by 17.4±19.6 % in the stabilized pathway, the ecosystems mitigate 10.6±1.4 % of national emissions in the stabilized pathway, more efficient than the fraction of 6.3±0.8 % in the transient pathway. To achieve the 1.5 ∘C warming target, our analysis suggests a higher allowable carbon budget for China under a stabilized pathway with reduced emissions in both CO2 and air pollutants.